Identifying key parameters for reliable assessment of entomopathogenic nematodes viability as affected by spray application stress-related factors - Beltrán-Martí, Roberto; Resecco, Marco; Gonella, Elena; Prieto, Sofía Victoria; Pittarello, Marco; Garcerá Figueroa, Cruz; Chueca, Patricia; Alma, Alberto; Gioelli, Fabrizio; Grella, Marco (Wiley, 2025)
BACKGROUND: Conventional pesticide application equipment (PAE) is used to apply entomopathogenic nematode (EPN)- based bioinsecticides, but their closed hydraulic systems could raise the temperature of the spray mixture up to 40 °C, potentially harming EPN, since temperatures above 30 °C can immobilize nematodes, reducing their infective capacity. This study aimed to identify the most suitable method to evaluate EPN viability under the effects of PAE technology.